Building better pediatric surgeons: A sentiment analysis of online physician review websites. (December 2022) - Butler, Liam R; Tang, Justin E; Hess, Skylar M; White, Christopher A; Arvind, Varun; Kim, Jun S; Allen, Abigail K; Ranade, Sheena C
Purpose: Physician review websites are a heavily utilized patient tool for finding, rating, and reviewing surgeons. Natural language processing such as sentiment analysis provides a comprehensive approach to better understand the nuances of patient perception. This study utilizes sentiment analysis to examine how specific patient sentiments correspond to positive and negative experiences in online reviews of pediatric orthopedic surgeons. Methods: The online written reviews and star ratings of pediatric surgeons belonging to the Pediatric Orthopaedic Society of North America were obtained fromhealthgrades.com . A sentiment analysis package obtained compound scores of each surgeon's reviews. Inferential statistics analyzed relationships between demographic variables and star/sentiment scores. Word frequency analyses and multiple logistic regression analyses were performed on key terms. Results: A total of 749 pediatric surgeons (3830 total online reviews) were included. 80.8% were males and 33.8% were below 50 years of age. Male surgeons and younger surgeons had higher mean star ratings. Surgeon attributes including "confident" (p < 0.01) and "comfortable" (p < 0.01) improved the odds of positive reviews, while "rude" (p < 0.01) and "unprofessional" (p < 0.01) decreased these odds. Comments regarding "pain" lowered the odds of positive reviews (p < 0.01), whereas "pain-free" increased these odds (p < 0.01). Conclusion: Pediatric surgeons who were younger, communicated effectively, eased pain, and curated a welcoming office setting were more likely to receive positively written online reviews. This suggests that a spectrum of interpersonal and ancillary factors impact patient experience and perceptions beyond surgical skill. These outcomes can advise pediatric surgeons on behavioral and office qualities that patients and families prioritize when rating/recommending surgeons online. Level of evidence: IV